A novel HDAC1/2 inhibitor suppresses colorectal cancer through apoptosis induction and cell cycle regulation. (25th January 2022) - Lee, Hsueh-Yun; Tang, Di-Wei; Liu, Chi-Yuan; Cho, Er-Chieh
Abstract: Colorectal cancer (CRC) is one of the leading causes of death around the world, and synthetic chemicals targeting specific proteins or various molecular pathways for tumor suppression, such as histone deacetylases (HADC) inhibitors, are under intensively studied. The target of HDAC involves in regulating critical cellular mechanisms and underpins the progression of anticancer therapy. However, little is known about the antitumor mechanisms of class I specific HDAC inhibitors in CRC. We structurally designed and synthesized benzamide-based compounds, examined their anticancer activity in several solid tumors, and identified compound 9 with high potential. Results from the in vitro enzyme and cell-based studies demonstrated that compound 9 as a selective HDAC1/2 inhibitor that possessed short-term and long-term suppression capacities against colorectal cancer cells. Investigation of molecular regulatory mechanisms of 9 in colorectal cancer cells by biological functional assays evidenced that treatment of compound 9 could activate apoptosis, induce cell cycle arrest, facilitate DNA damage process, and suppress cancer migration. A non-cancerous cell line and the in vivo zebrafish model were applied for safety evaluation. In summary, our results demonstrate that compound 9 is a promising lead drug worth further investigation for development of future cancer therapeutic agents. Highlights: The development of a selective HDAC inhibitor for colorectal cancer treatment. Benzamide-based compounds were structurally designed and synthesized. The compound induces apoptosis and cell cycle arrest in colon cancer cells. The compound suppresses cancer migration capacity and induces DNA damage process. Safety issues were evaluated by a non-cancerous cell line and a zebrafish model.